Cytomegalovirus Colitis in Primary Hypogammaglobulinemia With Normal CD4+ T Cells: Deficiency of CMV-Specific CD8+ T Cells - Agrawal, Sudhanshu; Khokhar, Amrita; Gupta, Sudhir (Frontiers in Immunology, 2019)
CMV colitis has been reported in immunocompromized patients with severe deficiency of CD4+ T cells and T cell functions. In this study we present an extensive immunological analysis in a patient with primary hypogammaglobulinemia and CMV colitis who had normal numbers of CD3+T, CD4+T and CD8+T cells, and normal T cell proliferative responses to mitogens and recall antigens. Naïve (TN), central (TCM) and effector (TEM) memory subsets of CD4+ and CD8+ T cells, Granzyme+ and Perforin+ CD8+ T cells, PD-1+ T cells, CD4 Treg, CD8 Treg, and CMV tetramer specific CD8+ T cells were analyzed with specific antibodies and isotype controls using multicolor flow cytometry. CD8 TEM, Granzyme+ and Perforin+, and PD-1 CD8+T cells were increased, whereas CD8 TN and CD8 TCM cells were decreased in the patient as compared to controls. CMV tetramer+ CD8+ T cells were decreased in the patient. These data demonstrate that a deficiency of CMV-specific CD8+ T cells even in the presence of normal CD4+ T cell numbers and normal T cell functions may predispose patients with primary hypogammaglobulinemia to CMV colitis.